Mild SARS-CoV-2 maternal infection in mice induces transient offspring neurodevelopmental aberrance - Wesley Tung; Matthew Yuen; Helen Cai; Hyesun Cho; Peiwen Lu; Harvey J. Kliman; Robert J. Homer; Alexa Herrerias; Nikkita Salla; Arianna Rodriguez Rivera; Yuting Liu; Kartik Pattabiraman; et al. (Proceedings of the National Academy of Sciences, 2026)
Maternal viral infection during pregnancy has been identified as a risk factor for psychiatric disorders and neurodevelopmental abnormalities in offspring. With cumulative SARS-CoV-2 infections now numbering in the hundreds of millions globally, there is a need to evaluate the effects of maternal SARS-CoV-2 infection on offspring brain development and behavior. We developed a mouse model of mild COVID-19 during pregnancy in which SARS-CoV-2 infection is restricted to the respiratory tract. Infected mothers did not show weight loss or changes in litter size, but did exhibit detectable local and systemic immune responses, including placental inflammation. Characterization of the offspring’s cerebral cortex revealed transcriptomic changes in the fetus at E15 and on postnatal day 5 (P5), but no gross alterations in cytoarchitecture, synaptic density, or microglial abundance. We did not detect any significant changes in open-field or novel object recognition tests in P50 offspring born to SARS-CoV-2-infected dams. These findings suggest that mild maternal respiratory SARS-CoV-2 infection induces soluble factors that mediate placental inflammation and transient cerebral cortex alterations in offspring that resolve by later childhood.